República das Penas: a construção do repertório imagético da República nas páginas das revistas o Mequetrefe, Revista Illustrada e Don Quixote (1889-1902) - Pereira, Washington Kuklinski (2016)
This paper aims to study how the Brazilian Republic was represented in caricatures that circulated in the press of Rio de Janeiro between the years of 1889 and 1902. Therefore, it is proposed to understand the universe around the production of graphic arts in the Press of Rio de Janeiro in the nineteenth century from the 1840s up to 1902. Thus, the relations between the producers of magazine caricatures and your readers are presented. We analyze the formation of the reading public through the press by itself, which was leading to imaginary consolidation over Republicans symbols since 1889. We investigate how the current media Magazine and The Mequetrefe and Revista Illustrada were the instrumental for popular legitimacy of the republican government system through caricatures with a lot of symbolic elements of the Republic. Also, realize as the Republic used the news means for the consolidation of its Heroes. We also study how the magazines Mequetrefe, Don Quixote and Revista Illustrada did the press coverage about the Federal Elections and the political municipality of Rio de Janeiro way of life during the Republic up to the year of 1902